2021
DOI: 10.1186/s12877-021-02050-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for shared decision making in older patients with multiple chronic conditions: a systematic review

Abstract: Background The aim of this study was to describe barriers and facilitators for shared decision making (SDM) as experienced by older patients with multiple chronic conditions (MCCs), informal caregivers and health professionals. Methods A structured literature search was conducted with 5 databases. Two reviewers independently assessed studies for eligibility and performed a quality assessment. The results from the included studies were summarized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 75 publications
(259 reference statements)
3
86
0
1
Order By: Relevance
“…Previous studies with GPs reported constraints on personalised care driven by an expectation to follow clinical guidelines (50)(51)(52)(53), with potentially inappropriate treatment and polypharmacy resulting (12,28,52,(54)(55)(56). Although differences in healthcare setting must be acknowledged when drawing comparisons with UK general practice, a focus group study in the United States of America explored a broader perspective by including other primary care clinicians as participants.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Previous studies with GPs reported constraints on personalised care driven by an expectation to follow clinical guidelines (50)(51)(52)(53), with potentially inappropriate treatment and polypharmacy resulting (12,28,52,(54)(55)(56). Although differences in healthcare setting must be acknowledged when drawing comparisons with UK general practice, a focus group study in the United States of America explored a broader perspective by including other primary care clinicians as participants.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Prior work describing this process more globally found that decisions are highly varied, with few generalizable conclusions for multimorbidity [ 21 , 32 ]. In one review, nearly two-thirds of the studies excluded patients with multimorbidity [ 32 ]; Other reviews have focused on specific facets of decision-making such as collaborative shared-decision making [ 33 , 34 ]. Heterogeneity in the decision-making literature may also due to an emphasis on care coordination in multimorbidity care, [ 35 , 36 ] which requires input from other care team members than physicians.…”
Section: Discussionmentioning
confidence: 99%
“…It can be by paying attention and listening to their suggestions about their treatment and care. Many decisions are made without patient participation (Pel-Little et al 2021 ). Supporting patients’ flexibility can be about, in dialogue with the person concerned, finding ways for him/her to adapt life to new or changed conditions.…”
Section: Discussionmentioning
confidence: 99%